2016
DOI: 10.1108/oth-09-2015-0061
|View full text |Cite
|
Sign up to set email alerts
|

Promoting multicultural literacies through game-based embodiment: a case study of counselor education students and the role-playing game Oblivion

Abstract: Purpose -This study aims to build on Gee's (2003) earlier question exploring specifically the learning processes associated with broadening cultural empathy and exploring personal bias through gameplay in the role-playing game, Oblivion. Design/methodology/approach -Methodology for this case study (Stake, 1995) was informed by narrative (Reissman, 2001) methods that focused on collecting descriptions of the unique experiences of participants while being engaged in gameplay and their personal reflections synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…Their hometown was assigned on the basis of the largest city. These customization options, while narrow, were intended to generate parasocial connections, and in doing so, facilitate social learning (Anderton and King, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their hometown was assigned on the basis of the largest city. These customization options, while narrow, were intended to generate parasocial connections, and in doing so, facilitate social learning (Anderton and King, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Younger users tend to identify more strongly with mediated characters in general (Blinka, 2008), and strengthening the parasocial connections between users and characters additionally contributes to social learning (Dunn, 2017). Making characters customizable enhances this sense of connection, and feeling connected to characters involved in intergroup contact is related to more positive attitudes toward the outgroup (Anderton and King, 2016). Subjects “move closer to role adoption and empathy when they must act on behalf of the individual, group, or institution they are simulating” (Stover, 2005: 211).…”
Section: Role-playing and The Formation Of Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…Video games also provide players with a "safe" place where they can acquire culture and play with cultural identities in a virtual environment that realistically imitates real life (Zielke et al, 2009). These realistic ingame environments provide a space where gamers can be open and vulnerable, question their beliefs, and increase their empathy for the culturally different other (Anderton & King, 2016).…”
Section: Discussion Of Video Games' Impact and Outcome From The Intermentioning
confidence: 99%
“…Deaton et al (2005) and Zielke et al (2009) used content design to test how serious games using IVET help to acquire culture-specific knowledge. Lane et al (2008) (Pandey et al, 2007) and The Elder Scrolls IV: Oblivion (Anderton & King, 2016), except for Crogan (2008), who concluded that the educational simulator Real Lives enhances understanding of global world processes. All authors reported positive outcomes of their studies.…”
Section: Knowledge Acquisition Outcomementioning
confidence: 99%